DEVELOPMENT OF DOMINO CARD MEDIA TO IMPROVE HIGH-LEVEL THINKING ABILITY IN UNDERSTANDING THE CONCEPT OF FRACTIONS - Suherman Priatna; Deni Iriyadi; Muhamad Toha (LPPM Universitas Negeri Jakarta, 2022)
This study aims to develop domino card learning media to improve higher order thinking skills in fractional material. This study uses an R&D approach to produce learning media products. The subjects in this study consisted of 4th grade students at SDN Ciandur 2 for the 2020-2021 academic year, grade 4 teachers at SDN Ciandur 2 and experts or practitioners, while the object in this study was the domino card media which is the development of domino media. This research design uses a 4D development model developed by Thiagrajan which consists of four stages, including define, design, develop, and disseminate. The results showed that the mastery of learning obtained results that the domino card media users had a positive influence on student learning outcomes. This is indicated by the students' learning mastery who reached a percentage of 87%. Thus the development of domino card media can be said to be effective for use in class IV fraction material at SDN Ciandur 2.